Primary geological characteristics, advances in exploration and production, and strategies of coalbed methane in South China - Tao GUO; Yatong ZHOU; Xiaobo JIN; Xiaokang GAO; Xingping PENG (Meitian dizhi yu kantan)
Objective and Methods South China contains abundant coalbed methane (CBM) resources from numerous, superimposed, thin coal seams, serving as a significant replacement for China’s CBM exploration and production in the future. Despite significant progress in recent years, the CBM industry still faces several challenges in comprehensive and effective production. To accelerate its development, this study summarizes the primary geological characteristics of CBM resources in South China, organizes the current status and advances in CBM exploration and production in this region, and proposes corresponding technical strategies. ResultsThe results indicate that the abundant CBM resources in South China exhibit coal seams characterized by numerous thin layers, a considerable cumulative thickness, moderate to high thermal maturity, high gas content, high saturation in deep parts, and abundant free gas, as well as complex tectonic conditions and coal structures. The exploration and production of these resources have undergone three stages: resource surveys and technology reference (1989‒2009), technological exploration (2010‒2020), and technical upgrades and tackling challenges in deep CBM (2021‒the present). Notably, the current exploration and production are in the stage of enhancing of the understanding and geological theories on deep CBM, along with upgrading and optimizing the adaptive fracturing with fractures effectively propped. These are expected to contribute to the rapid development of the CBM industry in South China. ConclusionsBased on the geological characteristics of CBM in South China, this study proposes four suggestions for CBM development: (1) It is necessary to intensify seismic exploration efforts, select optimal tectonically stable areas, conduct production capacity construction while assessing, and implement rolling production based on well groups. (2) It is recommended to implement large-scale commingled production of multiple coal seams by optimizing pay zone combinations. (3) Multistage fracturing of horizontal wells should be adopted for dominant coal seams. (4) It is necessary to advance the exploration assessment of deep CBM resources. Significant pathways to large-scale CBM production in South China include taking advantage of multiple coal seams, implementing reservoir stimulation through fracturing with fractures effectively propped, and accelerating geological assessment and target area selection of deep CBM resources.